Legal and institutional barriers to optimal financial architecture for new economy firms in developing countries - Danny Cassimon; Peter-Jan Engelen (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2002)
This paper reviews the obstacles for an appropriate financial architecture of new economy firms in developing countries by reviewing the theoretical and some preliminary empirical underpinnings of the importance of legal and institutional barriers. Apart from the more conventional institutional and legal barriers, which are advanced by the recent law and finance literature, the analysis in this paper focuses on the importance of the ICT environment, as a potentially important barrier to the development of the business sector in general, and new economy firms in particular. This preliminary analysis confirms the importance of this ICT environment for asset allocation (and the creation of intangibles) for the financial structure and, ultimately, for firm growth.
Keywords: G31; G32; K10; O4; 330; developing countries; new economy; ICT; law and finance; legal constraints; Informationstechnik; Unternehmensfinanzierung; Wirtschaftsrecht; Entwicklungsländer; New Economy